Producción de hortalizas orgánicas para la seguridad alimentaria y nutricional de la escuela Pedro Naula Pasaje - Sáenz Salinas, Ángel Eduardo (2010)
In the year 2009 during the months March until August in the school Pedro Toribio Naula Vega, located in the place San Antonio of Chaguana, canton Pasaje, province of El Oro realized the present work which targets were: To encourage of organic vegetables production for the food and nutritional safety of the school “ Pedro Naula “ Pasaje. To transform to the project in center of education, where across the training it is learned observing and practicing. To encourage to that the project is answered in the hearths of the family parents involved in the project. I take a base line, by means of the application to the children and family parents, with which there was obtained information that allowed taking preliminary decisions with regard to the implementation of the orchard and the process of training. After finished the field work the collaborators of the project, have the safety of which for the preparation of a good organic credit it is needed from organic garbage, being constituted in the principal raw material in the making of credits, the implementation of the orchards in his hearths in the 70% of participants, it allowed to apply the skills learned in the orchard model, as the possibility of working along with his parents and brothers working in group the 93%, of equal form the quality of the obtained product, since they are organic, healthy and nourishing vegetables obtained of an economic and easy form, and by means of these results to achieve a good, balanced and cheap feeding. For the evaluation of the project, they were realized field days, where I am evident in the children, and of the same way in the teacher and family parents a big satisfaction for the obtained results with the 85% of interest by the works } farming, as also a feeling of gratitude towards the persons in charge of the program, the person, the Regional Union of Rural Organizations of the Coast UROCAL and of the Technical University of Machala. Finally it is called to reflecting to the related institutions so that projects of equal magnitude are implemented in the rural Schools that receive the benefit of the government, across the breakfast and school lunch, the orchard will allow the progress in the nutrition of the children.